Human Capital Development of Lecturers' Human Resources - Saikhoni Saikhoni; Yulianto Yulianto; Dian Rachmawati (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine the development of human capital of lecturers at the University of Muhammadiyah Pringsewu. This research is a qualitative research by obtaining data through in-depth interviews with the Human Resources department. The results obtained are that in order to achieve these goals, the steps that need to be taken include planning, organizing, directing and controlling in higher education